The Beaman Distribution: A New Descriptive Model for the Size Distribution of Incomes - Maclachlan, Fiona C.; Reith, John E. (Journal of Income Distribution®, 2008)
A new two-parameter descriptive model for the size distribution ofincomes is presented. The Beaman distribution, originally found to describethe relationship between prices and sales volumes of textiles andrelated products, is shown to fit closely US Census data on individualincomes over the past twenty years. The two parameters of the modelrepresent the minimum and median levels of income. An important advantageof the Beaman distribution over other two-parameter modelsis that negative incomes can be accounted for.